2004
DOI: 10.1093/intimm/dxh073
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of MHC II-independent CD4+ T cells, IL-4 and STAT6 in contact hypersensitivity induced by fluorescein isothiocyanate in the mouse

Abstract: Contact hypersensitivity (CHS) induced by a hapten is thought to be mediated by T helper type 1 (Th1) cells. However, FITC can induce contact allergy in vivo, and in vitro studies suggest that this response is Th2-type driven. We compared CHS reactions induced by FITC or dinitrofluorobenzene (DNFB), a well-known Th1 inducing hapten, in Balb/c mice, C57/B6 mice, and several gene knock-out mice, and investigated the role of Th1/Th2 cytokines, T cell populations, eosinophils, and mast cells. Balb/c mice (Th2 domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
99
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 48 publications
7
99
0
3
Order By: Relevance
“…To determine how CGRP augments the FITC-induced CHS, we studied the regulatory effect of CGRP on T cells in vivo. It has been reported that FITC-induced CHS involves response to Th2-mediated inflammation (26,27) and that IL-4 is essential for this response (27). Consistent with this report, we observed that the FITC-induced CHS response was remarkably suppressed in IL-4-deficient mice (data not shown); therefore, IL-4 appears to play a critical role in FITC-induced CHS.…”
Section: Cgrp Regulates the Fitc-induced Chs Response Via Regulation supporting
confidence: 90%
“…To determine how CGRP augments the FITC-induced CHS, we studied the regulatory effect of CGRP on T cells in vivo. It has been reported that FITC-induced CHS involves response to Th2-mediated inflammation (26,27) and that IL-4 is essential for this response (27). Consistent with this report, we observed that the FITC-induced CHS response was remarkably suppressed in IL-4-deficient mice (data not shown); therefore, IL-4 appears to play a critical role in FITC-induced CHS.…”
Section: Cgrp Regulates the Fitc-induced Chs Response Via Regulation supporting
confidence: 90%
“…One of small chemical haptens is dinitrofluorobenzene (DNFB), which is associated with the activation of Th1 cells. Upon challenging the skin with DNFB in mice sensitized with DNFB, DNFB-specific T cells are recruited to the skin and produce Th1 cytokines, including IFN-g and IL-2 after challenge, indicating that Th1 cells are important in DNFB-induced CHS response (3). In contrast, previous studies have shown that FITC-induced CHS is Th2 dominant (3)(4)(5)(6).…”
mentioning
confidence: 95%
“…Upon challenging the skin with DNFB in mice sensitized with DNFB, DNFB-specific T cells are recruited to the skin and produce Th1 cytokines, including IFN-g and IL-2 after challenge, indicating that Th1 cells are important in DNFB-induced CHS response (3). In contrast, previous studies have shown that FITC-induced CHS is Th2 dominant (3)(4)(5)(6). When FITC was used as a hapten, Th2-like response was observed with an IL-4/IFN-g ratio of 25, whereas more IFN-g than IL-4-secreting cells were found in draining lymph nodes from DNFB-sensitized mice with an IL-4/IFN-g ratio of 0.026 (4).…”
mentioning
confidence: 99%
“…From an immunologic perspective, CHS can be considered as a prototype of T-cell-mediated delayed-type hypersensitivity and is a reliable in vivo approach to follow the whole process of immune responses to some haptens where CD4 ϩ T cells are thought to play a pivotal role. 51,52 One mechanism that may account for defective MHC-II-restricted stimulation of T cells in vivo by Ag-loaded ICSBP Ϫ/Ϫ BM-DCs may stem from a defective ability of these cells to migrate from the injection site to the draining LN. This view is based on the observations that ICSBP Ϫ/Ϫ BM-DCs express low levels of CCR7 as well as impaired chemotactic response to the CCR7 ligands Mip-3␤ and 6CKine.…”
mentioning
confidence: 99%